Legal Organization of The Electronic Money Wallet - Abdul-Qader, Dana Hama Baqy; Mahmud, Awesta Burham (Journal of Legal and Political Studies, 2022)
The electronic money wallet is one of the innovations brought about by technological progress in the field of communication and information. This method provided the possibility of completing transactions easily and its use allowed the good provision of services at all commercial levels, as it performs the functions that traditional money performs, but the transactions that are carried out through it are characterized by advantages It is represented in the ease of achievement and the lack of effort, costs and time limitation, and from this point of view, this research deals with the nature of this wallet and the legal effects of dealing with it, to assess the position of the Iraqi legislator in comparison with the comparative legislation, and the research reached a number of conclusions and recommendations in order to serve the optimal and security use of the electronic money wallet.
Keywords: electronic money; technological progress; traditional money; legal effects; Iraqi legislator